Non-Elite Chinese Catholic Converts’ Formation of Pragmatic Identity in the Course of Religious Interactions: A New Analysis of a 17th Century Manuscript Bingyin huike 丙寅會課 (Teaching Sessions in 1686) - Zhenxu Fan (Religions, 2025)
Through a critical analysis of one section of a 17th century Chinese manuscript, this article examines the formation of pragmatic identity of non-elite Roman Catholic Chinese converts, who simultaneously identified themselves as Confucians and Catholics within the culture of “Three Teachings synthesized into one system” (sanjiao heyi 三教合一) in traditional Chinese society. This investigation explores how these converts formed their pragmatic identity during their adaptation of Catholic beliefs and practices into a complex and dynamic context of interreligious interactions. The texts under examination are two essays in the Bian chizhai (辨持齋, Debating on Fasting) section in the Bingyin huike (丙寅會課, Teaching Sessions in 1686), composed in a Chinese Catholic seminarian community established and administered by Jesuit missionaries in Nanjing (南京). This interdisciplinary study not only provides a critical examination of the manuscript, which has not yet been extensively researched, but also offers a novel understanding of non-elite converts’ identity formation through the lens of pragmatic identity theory, drawing inspiration from American Pragmatism. It contributes to our contemporary understanding of non-elite Chinese Christian converts’ quest for identity amidst intercultural interactions between mainstream and marginal religions in 17th century Qing China.